Polysaccharide extracted from Chinese white wax scale ameliorates 2,4-dinitrochlorobenzene-induced atopic dermatitis-like symptoms in BALB/c mice - Lin Lin; Yiwei Zhou; Huifang Li; Dejian Pang; Liyun Zhang; Xiao Lu; Zhengliang Chen; Xiaoshan Zhao; Daming Zuo; Ledong Sun (Elsevier, 2017)
Atopic dermatitis (AD) is a common inflammatory skin disease with high rates of morbidity and is associated with erythema, pruritus, scaling of affected areas of skin. It is extremely important to introduce a therapeutic agent which has significant anti-inflammatory effect with less side-effect for treatment of AD. This study evaluated the effect of a natural compound from herbal extracts, the crude polysaccharide extracted from the white wax scale (CWPS), on AD-like mice. Repeated applications of 2,4-dinitrochlorobenzene (DNCB) were performed on ear and dorsal skin of BALB/c mice to induce AD-like symptoms and skin lesions. Oral administration of CWPS decreased serum IgE level and limited the infiltration of mast cells and eosinophils to the dermal tissues in the DNCB-induced AD mice. In addition, CWPS reduced Th1 and Th17 responses, leading to an attenuated cutaneous inflammatory response. Furthermore, in vitro study also demonstrated that CWPS limited T cell activation and cytokines (i.e. IFN-γ and IL-17) production induced by DNCB. We conclude that CWPS attenuates DNCB-induced AD-like skin lesion through modulating T cell-elicited immune responses and CD4+ T cell polarization, and could be exploited as a new therapeutic approach for AD. Keywords: Atopic dermatitis, Polysaccharide, White wax scale, Inflammatory skin lesion, Th cells